Recuperação de solo contaminado por petróleo usando bioestimulação - Costa, Maria Valdete da (Universidade Federal Rural do Semi-Árido, 2015)
The study of areas contaminated by petroleum hydrocarbons recovery arose due to the large environmental impacts from accidents involving oil spills, in the extraction, transport in pipelines, vessels and industrial units. Lately, the bioremediation process has been an alternative to reduce or remedy contamination caused by oil in the environment using the stimulation of native soil microbial fertilizer. Thus, the objective was to evaluate the ability of bioremediation of soil contaminated with oily compounds using biostimulation technique as an alternative capable of adequately handling the contamination in soils resulting from oil spills. The soil was contaminated with oil in increasing doses of 0, 1, 3, 5 and 10 % (w / w) and NPK biostimulation in a single charge at the start of the experiment at concentration levels of 0, 250, 500, 1250 and 2500 kg ha-1. The experiments were performed for 105 days and every 7 days determined the production of C-CO2. As best results for the production of C-CO2, gave a value of 3539.40 mg kg-1 at doses of 9.20 % oil and 2435 kg ha-1 for NPK
Soil contaminated by petroleum recovery using biostimulation
Keywords: Bioremediation; Fertilizers; Nutrients; NPK; Biorremediação; Fertilizantes; Nutrientes; NPK; CIENCIAS BIOLOGICAS::ECOLOGIA